Cambial phenology in Juniperus przewalskii along different altitudinal gradients in a cold and arid region. (1st February 2018) - Zhang, Junzhou; Gou, Xiaohua; Pederson, Neil; Zhang, Fen; Niu, Haoge; Zhao, Shoudong; Wang, Fang
Abstract: Knowing more precisely the cambial phenology and wood formation dynamics of trees can lead to a better understanding on how trees react to short-term changes in environmental conditions. Such an understanding could also shed light on the physiological foundation of climate–growth interactions at a regional scale. Although it has been documented that temperature is an important factor determining the cambial phenology in cold and humid climates, there is less agreement on the driver(s) that trigger the onset and end of wood formation in cold and arid climates. Here, the phenological traits of cambial activity and xylem formation were analyzed biweekly along an altitudinal transect ranging from 3580 to 3980 m above sea level, a transect that covers the distribution of Qilian juniper ( Juniperus przewalskii Kom.) along a slope of the Tibetan Plateau. Cambial phenology and the duration and rate of wood formation were assessed from anatomical observations during the growing season of the developing xylem obtained from microcores collected from the stem of 10 trees total in 2012 (five at two altitudes each) and 25 trees (five at five altitudes each) in 2013. We found that the onset of wood formation was significantly correlated with altitude in 2013, with onset beginning 8.2 days earlier with every 100 m decrease in elevation. The change in onset with elevation corresponds to a change of 14.1 days °C –1 when adjusted for the monitored altitudinal lapse rate of −0.58 °C per 100 m. The duration of wood formation lasted from mid-May to mid-August, with the length of the 2013 growing season decreasing from 97 to 65 days from low to high elevation. Although the end of growing season appeared minimally related to altitude during both growing seasons, differences in end of wood production and wood formation between the two growing seasons were significant. It appears that summer drought conditions constricted the end of growing season across all elevations along our transect in 2013. Sensitivity analysis found xylem growth was positively correlated with rate and duration of wood production, with the former explaining most variability in growth. Our findings provide new data on the timing and duration of wood formation and help quantify the potential impacts of global warming on tree growth and productivity in cold and arid regions.